Contribution of the MHC region to the familial risk of coeliac disease. Issue 9 (1st September 1999) - Bevan, S; Popat, S; Braegger, C P; Busch, A; O'Donoghue, D; Falth-Magnusson, K; Ferguson, A; Godkin, A; Hogberg, L; Holmes, G; Hosie, K B; Howdle, P D; et al.
Abstract : Susceptibility to coeliac disease is genetically determined by possession of specific HLA-DQ alleles, acting in concert with one or more non-HLA linked genes. The pattern of risk seen in sibs and twins in coeliac disease is most parsimonious with a multiplicative model for the interaction between the two classes of genes. Based on a sib recurrence risk for coeliac disease of 10% and a population prevalence of 0.0033, the sib relative risk is 30. To evaluate the contribution of the MHC region to the familial risk of coeliac disease, we have examined haplotype sharing probabilities across this region in 55 coeliac disease families. Based on these probabilities the sib relative risk of coeliac disease associated with the MHC region is 3.7. Combining these results with published data on allele sharing at HLA, the estimated sib relative risk associated with the MHC region is 3.3. Therefore, the MHC genes contribute no more than 40% of the sib familial risk of coeliac disease and the non-HLA linked gene (or genes) are likely to be the stronger determinant of coeliac disease susceptibility.